Emerging roles for brain drug-metabolizing cytochrome P450 enzymes in neuropsychiatric conditions and responses to drugs. (2nd July 2016) - Toselli, Francesca; Dodd, Peter R.; Gillam, Elizabeth M. J.
Abstract: P450s in the human brain were originally considered unlikely to contribute significantly to the clearance of drugs and other xenobiotic chemicals, since their overall expression was a small fraction of that found in the liver. However, it is now recognized that P450s play substantial roles in the metabolism of both exogenous and endogenous chemicals in the brain, but in a highly cell type- and region-specific manner, in line with the greater functional heterogeneity of the brain compared to the liver. Studies of brain P450 expression and the characterization of the catalytic activity of specific forms expressed as recombinant enzymes have suggested possible roles for xenobiotic-metabolizing P450s in the brain. It is now possible to confirm these roles through the use of intracerebroventricular administration of selective P450 inhibitors in animal models, coupled with brain sampling techniques to measure drug concentrations in vivo, and modern neuroimaging techniques. The purpose of this review is to discuss the evidence behind the functional importance of P450s from the "xenobiotic-metabolizing" families, CYP1, CYP2 and CYP3 in the brain. Approaches used to define the quantitative and qualitative significance of these P450s in determining tissue-specific levels of xenobiotics in brain will be considered. Finally, the possible roles of these enzymes in brain biochemistry will be examined in light of the demonstrated activity of these enzymes in vitro and the association of particular P450 forms with disease states.